Coronary angiography and percutaneous coronary intervention in cardiac arrest patients without return of spontaneous circulation. (June 2022) - Rob, Daniel; Kavalkova, Petra; Smalcova, Jana; Kral, Ales; Kovarnik, Tomas; Zemanek, David; Franěk, Ondrej; Smid, Ondrej; Havranek, Stepan; Linhart, Ales; Belohlavek, Jan
Abstract: Objectives: This study aimed to examine coronary angiography (CAG) findings, percutaneous coronary intervention (PCI) results and outcomes in out-of-hospital cardiac arrest patients (OHCA) without return of spontaneous circulation (ROSC) on admission to hospital. Methods: We analyzed the OHCA register and compared CAG, PCI, and outcome data in patients with and without ROSC on admission to hospital. Results: Between January 2012 and December 2020, 697 OHCA patients were analyzed. Of these, 163 (23%) did not have ROSC at admission. Patients without ROSC were younger (59 vs. 61 years, p = 0.001) and had a longer resuscitation time (62 vs. 18 minutes, p < 0.001) than patients with ROSC. Significant coronary artery disease was highly prevalent in both groups (65% vs. 68%, p = 0.48). Patients without ROSC had higher rates of acute coronary occlusions (42% vs. 33%, p = 0.046), specifically affecting the left main stem (16% vs. 1%, p < 0.001). PCI was performed in 81 patients (50%) without ROSC and in 295 (55%) with ROSC (p = 0.21). The success rate was 86% in patients without ROSC and 90% in patients with ROSC (p = 0.33). Thirty-day survival was 24% in patients without ROSC and 70% in patients with ROSC. Conclusions: OHCA patients without ROSC on admission to hospital had higher acute coronary occlusion rates than patients with prehospital ROSC. PCI is feasible with a high success rate in patients without ROSC. Despite prolonged resuscitation times, meaningful survival in patients admitted without ROSC is achievable.